Development of Interactive Media Based on Mathflash Applications for Learning Materials of Sequences and Senses - Fadhillah, Dinar; Gunadi, Farid; Ismunandar, Denni (Universitas Wiralodra, 2025)
This study aims to determine the results of initial observations regarding the material for sequences and series to students and teachers, to explain the identification of the need for Mathflash applications for sequences and series materials and to produce interactive media based on the Mathflash application for sequence materials. and sequences via a viable and effective App Inventor. The type of research used in this study is Research and Development (R & D). Researchers used the development method according to Borg and Gall with 8 stages of development, including: (1) initial observation; (2) plans; (3) making products; (4) product validation test; (5) limited scale test; (6) limited scale test revision; (7) field test ; (8) analysis of field results, with data collection techniques used are interview guidelines and expert questionnaires (observation sheets) and questionnaires for class XI students on a limited scale test, data analysis techniques used are qualitative and quantitative descriptive statistics with using the validity of the Aiken index. Then to analyze the effectiveness of the media with a posttest given to students. Based on the results of the media feasibility test, which was assessed by 5 experts, the overall average score of the three feasibility aspects was 3.53 in the eligible category, and the media assessed by 6 students got the overall average score for the two feasibility aspects of 4.54 in the eligible category. Testing the effectiveness of learning media using a one- sample t-test resulted in tobs = 5.574 and tc= 1.690. So, tobs > tc then reject Ho, so that interactive media based on the Mathflash application material is effectively used in learning.